Proceedings of the symposium on climate and rice (IRRI, 1976)
The book presents the climatic environment in which rice is grown commercially or experimentally; examines the influence of each of the climatic variables on different phases of rice growth, and on the incidence of pests and diseases; and identifies means to further increase and stabilize rice yields under variable climatic conditions